2022
DOI: 10.1007/s13593-022-00800-9
|View full text |Cite
|
Sign up to set email alerts
|

Ecological engineering for rice pest suppression in China. A review

Abstract: Ecological engineering for pest suppression aimed at promoting ecosystem services of biological control, involves a range of environmentally-benign approaches to conserve and promote arthropod natural enemies and suppress pest populations, and thus reduce the need for insecticide use. Major components in rice pest management involve providing vegetation that favors parasitoid overwintering during the fallow seasons, growing nectar-producing flowering plants on the rice bunds to enhance the biocontrol function,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…and chemical properties of the ridge have the greatest effect on plant and animal diversity [ 39 ]. In addition, as one semi-natural habitat type, the ridge also provides a better habitat for plants and animals than the interior of the field [ 44 , 45 ]. Under suitable environmental conditions, the greater the habitat area, the higher the biodiversity [ 46 ]; thus, a wider ridge represents a larger growth, development, and activity area, a more hidden space for organisms, and should have a higher diversity of plants and animals [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…and chemical properties of the ridge have the greatest effect on plant and animal diversity [ 39 ]. In addition, as one semi-natural habitat type, the ridge also provides a better habitat for plants and animals than the interior of the field [ 44 , 45 ]. Under suitable environmental conditions, the greater the habitat area, the higher the biodiversity [ 46 ]; thus, a wider ridge represents a larger growth, development, and activity area, a more hidden space for organisms, and should have a higher diversity of plants and animals [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that some of the benefits of ecological engineering (i.e., increasing natural enemy abundance or efficiency) could be achieved even where farmers make prophylactic insecticide applications (model 5, Figure 1). In such a case, ecological engineering would only be adopted because it 'counters' the negative effects of prophylactic applications (i.e., increasing resilience by preventing pest outbreaks in the face of intense, prophylactic insecticide use), although it might also bring other benefits to the system including providing habitat for wildlife, especially pollinators [7,37,44,45]. One drawback of resilience-or the perception of resilience-provided by flower strips in intensive systems, is that it could lead to even greater levels of pesticide use if flower strips are regarded as an 'insurance' (model 6, Figure 1) against pest resurgence, thereby allowing farmers to increase applications or apply insecticides indiscriminately.…”
Section: Integration Models For Flower Strips and Pest Management Wit...mentioning
confidence: 99%
“…Ecological restoration using flower strips or otherwise diversified habitat is expected to bring several benefits besides improving the natural regulation of arthropod pests [14,44,45]. Furthermore, as a restoration practice, farmers might have been expected to reduce their use of other pesticides because herbicides and fungicides are also hazardous to the environment and some products are associated with outbreaks of insect pests [40].…”
Section: Other Factors Determining the Success Of Flower Stripsmentioning
confidence: 99%
“…It is not clear whether these landscape‐level large semi‐natural habitats can compensate for the loss of biodiversity due to land consolidation. This question is relevant when managers are considering investing in agri‐environment measure (AEM) or Ecological Engineering (EE), such as planting grass or flower strips to enhance the linear habitats, as a way to conserve farmland biodiversity and ecosystem services (Horgan et al., 2016; Kleijn & Sutherland, 2003; Uthes & Matzdorf, 2013; Zhu et al., 2022; Zou, 2024). For example, a meta‐analysis based on European studies found that the effectiveness of AEM in improving pollinator diversity is determined by the ecological contrast (i.e.…”
Section: Introductionmentioning
confidence: 99%